COMPARISON OF SOXHLETATION AND MACERATION METHODS AGAINST LEVEL TOTAL FLAVONOID EXTRACT ETHANOL 96% LEAF CIPLUKAN (Physalis angulata) - Anisatul Maghfiroh Anisa; Mohammad Rofiq Usman; Dhina Ayu Susanthi (Indonesian Pharmacopeia Journal, 2025)
Leaf ciplukan has known public Indonesia as plant drug. Leaf ciplukan (Physalis angulata) contain secondary metabolite compounds, one of which is flavonoids. Flavonoid compounds from plants are obtained from various processes, one of which is process extraction with method soxhletation And maceration. Objective: Analyzing the differences Soxhletation and maceration methods on total flavonoid content of ethanol extract of ciplukan leaves (Physalis angulata). Method: The extraction process of the simple drug was carried out using the soxhlet method and maceration, follo wed by screening of flavonoid compounds against 96% ethanol extract of ciplukan leaves (Physalis angulata). Quantitative tests were conducted to determine the total flavonoid content of the leaves. Ciplukan (Physalis angulata) was carried out using the UV-Vis spectrophotometry method at a wavelength of wave 665 nm. Results: Phytochemical screening showed that the extracted ethanol extract use method soxhletation And maceration contain compound flavonoid proven with results screening from both of them positive. Level total flavonoid Which extracted use soxhletation method as much as 11 mgQE/g while extracted using the maceration method as much as 3 mgQE/g. Results from test statistics method T-Test known mark sig <0.05. Conclusion: Extraction with method soxhletation produce level total flavonoid Which more tall compared to the maceration method. This proves that soxhletation is a method best used to extract flavonoid compounds in ciplukan leaves (Physalis angulata)